Gambaran budaya keselamatan pasien di rumah sakit Izza Karawang Tahun 2024 - Dewi, Marhindayani; Damayanti, Rita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
This study was conducted to describe the patient safety environment developed by Izza Hospital, Karawang, using the Hospital Survey on Patient Safety Culture (HSOPSC) instrument developed by the Agency for Healthcare Research and Quality (AHRQ). The research method used a quantitative descriptive design with a survey approach, involving 326 respondents from medical and non-medical personnel who were directly related to patient care. The sampling technique was accidental sampling, and data were analyzed using univariate analysis for the frequency distribution of the 12 dimensions of patient safety culture. The findings showed that most respondents were nurses (62.9%) with 1-5 years of service (38%) and working hours >40 hours per week (64%). The assessment of the work unit showed the majority in the “good” category (56%), while the most patient safety reports were 1-2 reports per year (35%). Most indicators of patient safety culture showed positive responses, such as teamwork (97%) and open communication (66-81%). However, there were challenges in indicators such as response to errors and staff courage to ask critical questions. In conclusion, the patient safety culture at Izza Hospital is in the “good” category but needs specific improvements in certain dimensions to support more optimal patient safety. These results provide insights for the hospital in formulating strategies for continuous improvement of patient safety culture.